Long non-coding RNA PCED1B-AS1 promotes the proliferation of colorectal adenocarcinoma through regulating the miR-633/HOXA9 axis. Issue 3 (1st March 2022) - Liu, Jianfeng; Qian, Jun; Mo, Qi; Tang, Liming; Xu, Qiang
ABSTRACT: Long non-coding RNA (lncRNA) PCED1B-AS1 was shown to play essential roles in human cancers, while its function in colorectal adenocarcinoma remains unclear. This study was carried out to investigate the function of PCED1B-AS1 in regulating the microRNA(miR)-633/HOXA9 axis in colorectal adenocarcinoma. The expression of PCED1B-AS1, miR-633 and HOXA9 was measured by quantitative real-time PCR (qRT-PCR) or Western blot analysis. Cell behaviors of colorectal adenocarcinoma cell lines were assessed by CCK-8, EdU, Transwell and flow cytometry assays. The interaction among PCED1B-AS1, miR-633 and HOXA9 was determined by luciferase reporter and RIP assays. Rescue experiments were performed to determine the regulatory axis in colorectal adenocarcinoma. Moreover, an animal model was established to verify the role of PCED1B-AS1. We found that PCED1B-AS1 was upregulated and miR-633 was downregulated in colorectal adenocarcinoma tissues and corresponding cell lines. Knockdown of PCED1B-AS1 inhibited cell proliferation and promoted apoptosis, while miR-633 inhibitor elevated proliferation and reduced apoptosis of cancer cell lines. In addition, overexpression of HOXA9 obviously attenuated the protective role of knockdown of PCED1B-AS1 or miR-633 mimics in colorectal adenocarcinoma progression. PCED1B-AS1 could negatively regulate the expression of HOXA9 by sponging miR-633. The in vivo experiments confirmed the role of PCED1B-AS1 and miR-633 in colorectal adenocarcinoma, as well as the regulatory relationship of this axis. Our results demonstrated that knockdown of PCED1B-AS1 inhibited the progression of colorectal adenocarcinoma by regulating the miR-633/HOXA9 axis. Graphical abstract: uf0001